Studi Kelayakan (Feasibility Studi) Relokasi UPT Puskesmas Dilang Puti Kabupaten Kutai Barat - Miharja, Ediyar; Sukmana, Mayusef; Ika Fikriah, Ika Fikriah; Rahmat, Rahmat Bakhtiar; Krispinus, Krispinus Duma (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2023)
The establishment or relocation of puskesmas requires a feasibility study in its planning. The feasibility study became the basis for the relocation of the Dilang Puti Puskesmas land, related to the determination of the Puskesmas Health Service Work Plan. The purpose of this community service is to conduct a feasibility study on the existence of the existing puskesmas building and analyze the relocation of the Dilang Puti Puskesmas. This community service method is to conduct a feasibility study of relocating the puskesmas in a new location. Primary data collection is carried out through location observation methods, focus discussion groups and skunder data collection is carried out through document search. The analysis was conducted by comparing the results of data collection with the Minister of Health Regulation No. 43 of 2019 through analysis of the current situation and analysis of the situation of the puskesmas relocation site. Results: Analysis of the current situation of the existing puskesmas building is: Building layout, building component requirements, infrastructure requirements, the existence of the Dilang Puti puskesmas building that needs to be developed to anticipate population development and development progress. Relocation land that meets the requirements is 3 (three) land lands. Conclusion: The existing Dilang Puti health center building is not possible to be developed in the future to anticipate population development and development progress. There are three land areas that allow for the development of the Dilang Puti health center, the 3rd alternative location is the main choice. Keywords: Public Health Care, Feasibility Study